2010
DOI: 10.1111/j.1472-765x.2010.02865.x
|View full text |Cite
|
Sign up to set email alerts
|

Enumeration of Vibrio parahaemolyticus in oyster tissues following artificial contamination and depuration

Abstract: Aims:  To evaluate enumeration of Vibrio parahaemolyticus in oyster tissues following artificial contamination and depuration. Methods and Results:  After inoculating with V. parahaemolyticus (ATCC 17802) and incubating for 24 h, the contaminated oysters were depurated with artificial seawater for 14 days. At each step, the tissue homogenate supernatants of oysters were spread‐plated onto thiosulfate‐citrate‐bile salt‐sucrose agar, followed by colony confirmation by the polymerase chain reaction. The pathogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 29 publications
4
19
0
Order By: Relevance
“…It is possible that different routes of inoculation might affect the distribution of V. parahaemolyticus in oyster tissues. For example, in natural oysters, V. parahaemolyticus and Vibrio vulnificus appear to accumulate at higher densities in the digestive glands than in other tissues (60,63). To account for this possibility, V. parahaemolyticus growth rates using injected oysters were compared with natural levels of the bacteria in model evaluation experiments.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that different routes of inoculation might affect the distribution of V. parahaemolyticus in oyster tissues. For example, in natural oysters, V. parahaemolyticus and Vibrio vulnificus appear to accumulate at higher densities in the digestive glands than in other tissues (60,63). To account for this possibility, V. parahaemolyticus growth rates using injected oysters were compared with natural levels of the bacteria in model evaluation experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Over 107 CFU of aerobic bacteria per gram were found in retail oysters after 1 week storage at 4°C [31]. Furthermore, it has been reported that the bacteria were mainly accumulated in digestive glands and gills [2,6,10,11]. Therefore, more bacteria should be accumulated in those tissues compared to other types of oyster tissues.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that oysters filter large volumes of water during feeding and are able to bio-accumulate bacteria including food-borne pathogens from the surrounding water [1,2], therefore, oysters may be an important vehicle for dissemination of food-borne pathogens [3][4][5][6]. In the coastal cities of China, more than 60% of seafood tested positive for bacterial pathogens [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…These methods have included the use of V. vulnificus strains with specific antibiotic resistance, natural bioluminescence, radiolabeling, alkaline phosphatase activity, fluorescence, or a specific molecular marker (8,13,(20)(21)(22) 31). These marked strains are critical for ensuring that the data collected on the uptake or depuration rates of the added cells are accurate and that factors such as outgrowth or a lingering population of similar bacteria are not confounding the results.…”
mentioning
confidence: 99%
“…The "core" method is described first, followed by examples of deviation from this formula. The core method, elegant in its simplicity, is to grow the bacterial strain of interest to the desired concentration and seed an aquarium with a specific concentration of those bacteria, while allowing oysters within that aquarium to bioaccumulate the cells (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). The use of this method often yields similar results in which the bacteria are rapidly and significantly taken up by the oysters but quickly depurated to minimal or nondetectable levels within a few days (11,12,19,(22)(23)(24).…”
mentioning
confidence: 99%